KAJIAN SIFAT FISIKA DAN KIMIA TANAH ULTISOL PADA LAHAN KARET YANG TELAH MENGHASILKAN DENGAN BEBERAPA JENIS VEGETASI YANG TUMBUH DI KEBUN PTPN III SARANG GITING (The Study of Physical And Chemical Properties of Ultisol Soil on mature Rubber Land with Some - Doni Romanosa; Sumono Sumono; Achwil Putra Munir (Universitas Sumatera Utara, 2018)
ABSTRACT Physical and chemical soil characteritics are important factors for the growth of rubber plant. This research was aimed to study physical and chemical soil characteritics of the rubber plant with vegetations of harupat spikes, grass, taro and no vegetation in PTP. Nusantara III Sarang Giting. The observed parameters were soil texture, porosity, water content of field capasity, soil permeability, total Nitrogen, available Phospate, and land Potassium exchange.The results showed that the soil type was ultisol, with sandy loam texture and pH of 4,55-4,69 (acid). The vegetation soil had porosity of 55,42-56,36 % at a depth of 5 cm and 54,86-55,14 % at a depth of 25 cm. The water content of field capacity was ranged from 37,9-49,9 % at a depth of 5 cm and 35,1-47,5 % at a depth of 25 cm. Permeability was ranged from 3,40-4,72 cm/h. Total N was 0,07-0,11 %. P available was ranged from 15,10-17,70 ppm. K exchange of land was ranged from 0,57-0,76 me/100g. The soil with no vegetation had porosity of 55,42 % at a depth of 5 cm and 54,86 % at a depth of 25 cm. The water content of field capacity was 42,8 % at a depth of 5 cm and 42,2 % at a depth of 25 cm. Permeability was 4,72 cm/h. Total N was 0,10 %. P available was 17,12 ppm. K exchange of land was 0,67 me/100g. Keywords: Soil Physical And Chemical Properties, Vegetation, Ultisol ABSTRAK Sifat fisika dan kimia tanah merupakan faktor penting bagi pertumbuhan karet. Penelitian ini bertujuan untuk mengkaji sifat fisika dan kimia tanah ultisol pada lahan karet dengan vegetasi paku harupat, rumput, keladi dan tanpa vegetasi di Kebun PTP. Nusantara III Sarang Giting. Parameter yang diamati meliputi tekstur tanah, porositas, kadar air kapasitas lapang, permeabilitas tanah, N-total, P tersedia dan K tukar tanah. Hasil penelitian menunjukkan jenis tanah di daerah penelitian adalah ultisol bertekstur liat berpasir, lempung liat berpasir, dan lempung berpasir dengan pH 4,55-4,69 (masam). Tanah dengan vegetasi mempunyai porositas berkisar 55,42-56,36 % pada kedalaman 5 cm dan 54,86-55,14 % pada kedalaman 25 cm, kadar air kapasitas lapang 37,9-49,9 % pada kedalaman 5 cm dan 35,1-47,5 % pada kedalaman 25 cm, permebilitas berkisar 3,40-4,72 cm/jam, N-total 0,07-0,11 %, P tersedia 15,10-17,70 ppm, K tukar tanah 0,57-0,76 me/100g. Tanah tanpa vegetasi mempunyai porositas berkisar 54,96 % pada kedalaman 5 cm dan 54,16 % pada kedalaman 25 cm, kadar air kapasitas lapang 35,7 % pada kedalaman 5 cm dan 34,2 % pada kedalaman 25 cm, permebialitas berkisar 2,56 cm/jam, N-total 0,06 %, P tersedia 11,29 ppm, K tukar tanah 0,54 me/100g. Kata Kunci: Fisika dan kimia tanah, vegetasi, ultisol.